EXISTENCE OF ARTICLE 70 LETTER (C) OF LAW NUMBER 30 YEAR 1999 ON ARBITRATION AND ALTERNATIVES DISPUTE RESOLUTION AS A REASON FOR CANCELLATION ARBITRATION AWARD - Al-Anshori, Huzaimah; Handayani, Emi Puasa; Chasanah, Nur; Manfaluthi, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
The existence of Article 70 letter (c) of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution is still being debated. In its development, the article provides legal implications that are actually negative for dispute resolution institutions outside the court, the reasons for the disputing parties in the Arbitration forum are trickery as a reason for requesting the cancellation of the Arbitration decision and so that trickery can be used as a reason to cancel an Arbitration decision as in the District Court decision Number: 54 / Pdt.G / 2015 / PN.Kdr. the method used in this study is the normative research method, the statute approach, the case approach, the conceptual approach , the philosophical approach. Based on the considerations used, it appears that the Kediri City District Court wants to find out when evidence of a legal event exists and is made by parties who have a legal relationship in order to create a belief as a basis for making a decision in a civil case. Legally, making a request to annul the Arbitration decision submitted by the disputing parties for the reasons as stipulated in Article 70 letter (c) of the Arbitration Law no longer requires a Court decision for the reasons in case Number: 54/Pdt.G/2015/PN.Kdr. The Kediri City District Court has suspected that there was a trick carried out by PT. Fajar Parahiyangan at the Indonesian National Arbitration Board (BANI) Surabaya case Reg. No. 13/ARB/BANI-SBY/I/2015. The Kediri City District Court in determining the existence of a trick at the Indonesian National Arbitration Board (BANI) Surabaya Reg. No. 13/ARB/BANI-SBY/I/2013. The evidence of the disputing parties in A Statement Letter is one of the pieces of evidence submitted by one of the parties to the Indonesian National Arbitration Board (BANI) Surabaya.